Analysis of Special Guidance Teachers in Malang City Based on Teacher Competencies - Ediyanto, Ediyanto; Novianti, Ranti; Hastuti, Wiwik Dwi; Riswari, Fina; Rizqianti, Nindya Ayu; Jatiningsiwi, Tata Gading (Angstrom Centre of Education, 2023)
A Special Guidance Teacher is a teacher who has a special education/exceptional education background or who has received training in special education/exceptional education and is assigned to an inclusive school. A Special Guidance Teacher must be based on several main competencies such as pedagogic, personality, professional, and social. The purpose of this paper is to describe the situation in the field regarding the potential of accompanying teachers for Special Need Students based on the basic competencies of teachers. This is expected to encourage the process of realizing performance products that can support the quality of professional education as evidenced by the competencies possessed by Special Need Students and companion teachers along with adequate professional allowances according to the standard of living of a well-off society. The method used is the descriptive qualitative method. The research subjects were 3 Special Guidance Teachers and a Shadow with data collection techniques interview techniques, and literacy. Data analysis uses the Miles & Huberman (1992) interactive analysis model. Based on the results of the study, overall teacher competence in Special Guidance Teachers in Malang can be said to be quite good. In detail, the ability of Special Guidance Teachers competence in pedagogical and professional competence is still lacking, while the ability of Special Guidance Teachers in personality and social competence is good. Based on the research findings, there are several suggestions, among others: 1) For policymakers, it is hoped that the results of the study can be used to make new policies, conduct training, and coaching to improve the quality of teacher educators, especially for disabilities. 2) For Special Guidance Teachers, it is expected to utilize the research results as a reference to improve teacher competence to create disability-friendly schools. 3) For future researchers, it is hoped that research will be carried out more carefully and thoroughly on aspects of the needs and abilities of Special Guidance Teachers so that the competence of teachers with disabilities is better and more appropriate.